2013
DOI: 10.1016/j.jsb.2013.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies on full-length talin1 reveal a compact auto-inhibited dimer: Implications for talin activation

Abstract: Talin is a large adaptor protein that activates integrins and couples them to cytoskeletal actin. Talin contains an N-terminal FERM (band 4.1, ezrin, radixin, moesin) domain (the head) linked to a flexible rod comprised of 13 amphipathic helical bundles (R1–R13) that terminate in a C-terminal helix (DD) that forms an anti-parallel dimer. We derived a three-dimensional structural model of full-length talin at a resolution of approximately 2.5 nm using EM reconstruction of full-length talin and the known shapes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(141 citation statements)
references
References 65 publications
7
127
0
Order By: Relevance
“…4). Interestingly, the length of talin/L432G corresponds to ∼81 nm (21 nm/sin 15°), in good agreement with the recent estimate of the end-to-end length of talin in which all domains are folded (35). We surmise that the increased length of ∼16 nm observed in cells expressing wild-type talin could be due to their greater contractility relative to talin/L432G cells, which may lead to a partial unfolding of rod domains.…”
Section: Probing the Structural Role Of Talin By Recombinant Minitalinsupporting
confidence: 89%
See 1 more Smart Citation
“…4). Interestingly, the length of talin/L432G corresponds to ∼81 nm (21 nm/sin 15°), in good agreement with the recent estimate of the end-to-end length of talin in which all domains are folded (35). We surmise that the increased length of ∼16 nm observed in cells expressing wild-type talin could be due to their greater contractility relative to talin/L432G cells, which may lead to a partial unfolding of rod domains.…”
Section: Probing the Structural Role Of Talin By Recombinant Minitalinsupporting
confidence: 89%
“…S4A). Recent structural studies suggest that individual domains of the talin rod are highly modular (35), permitting us to generate "minitalins" analogs that vary in sequence from 29 to 58% of full-length talin. We refer to these by their nominal sequence lengths, e.g., T29 for the analog that contains 29% of the sequence of full-length talin (T100), and so on ( Fig.…”
Section: Probing the Structural Role Of Talin By Recombinant Minitalinmentioning
confidence: 99%
“…Electron microscopy observations have suggested that cytoplasmic talin is in a closed conformation (Molony and Burridge, 1985), and cryo-electron microscopy was used to generate a rolled-up dimer model, with talin heads packed at the centre of a doughnut-shaped structure that is unable to bind integrins (Goult et al, 2013a). Two intramolecular interactions between the head and rod have been mapped: between R9 and F3, masking IBS1 (Goksoy et al, 2008;Goult et al, 2009;Zhang et al, 2016), and between R1-R2 and F2-F3, potentially masking membranebinding regions of talin head (Banno et al, 2012).…”
Section: Regulation Of Talin Interactionsmentioning
confidence: 99%
“…The FERM domain of talin is atypical in that the first of the characteristic three subdomains (F1) is duplicated, adding a fourth subdomain at the N-terminus (F0) , a feature only shared with kindlins. The head is followed by an unstructured region (the 'linker'; ∼80 amino acids) and then the rod domain (∼2000 amino acids), which is formed of 13 helical bundle domains (R1-R13, containing 62 α-helices) each consisting of four or five α-helices Goult et al, 2013a). In some non-vertebrate organisms, talin has additional sequences beyond the 62nd helix; for example, Dictyostelium talin B contains a villin headpiece-like domain (Tsujioka et al, 1999), and a Drosophila variant extends talin by ∼300 amino acids (Senetar and McCann, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggests that talin adopts a donut-shaped structure in its auto-inhibited state 114 ( Fig. 2).…”
Section: Talinmentioning
confidence: 93%